Level of expression of the tomato rbcS-3A gene is modulated by a far upstream promoter element in a developmentally regulated manner. - Ueda, T (1989)
By Agrobacterium-mediated transformation we have demonstrated that a 1.10-kilobase promoter sequence from the tomato rbcS-3A gene confers light-inducible and organ-specific expression upon fusion to the bacterial chloramphenicol acetyltransferase gene. A biphasic expression profile was obtained by 5' deletion analysis of this promoter, indicating the presence of both positive and negative regulatory elements. A severe reduction in the level of expression was observed when the 5'-terminal 90 base pairs were deleted from the 1.10-kilobase promoter. DNA sequence elements responsible for light inducibility and organ specificity of the gene reside within the -374 base pairs of the proximal part of the promoter and the sequences spanning from -374 to -205 are essential for promoter function. The DNA sequences upstream from -374 modulate the level of expression in leaf tissue; this modulation is under developmental control.